A centralized directional distance model for efficient and horizontally equitable grants allocation to local governments. (June 2022) - Arocena, Pablo; Cabasés, Fermín; Pascual, Pedro
Abstract: This paper proposes a directional distance model for efficient resource allocation when there is a centralized decision maker who oversees all units. The model is designed to allocate grants from an upper-tier government to the municipalities under its jurisdiction. Local governments employ the grants together with levied local taxes to provide services to their citizens. The objective of our formulation is to optimize grants allocation across municipalities taking into account efficiency, effectiveness and horizontal fiscal equity criteria. The model easily allows the setting of alternative priorities of the central decision maker, thus permitting quantification of the trade-off between the potential increase in the provision of local services and its associated cost. The model is applied to the allocation of current grants in the autonomous community of Navarre in northern Spain. Highlights: A directional distance model for centralized resource allocation and efficient target setting is proposed. The model is designed to allocate grants from an upper-tier government to municipalities under its jurisdiction. Grant allocation across municipalities achieves financial sufficiency and horizontal equity or fiscal equalization. The model is applied to simulate the allocation of grants to municipalities by the regional government of Navarre, Spain.